2010
DOI: 10.1002/jbmr.292
|View full text |Cite
|
Sign up to set email alerts
|

Once-yearly zoledronic acid and days of disability, bed rest, and back pain: Randomized, controlled HORIZON Pivotal Fracture Trial

Abstract: The objective of this study was to determine the effect of once-yearly zoledronic acid on the number of days of back pain and the number of days of disability (ie, limited activity and bed rest) owing to back pain or fracture in postmenopausal women with osteoporosis. This was a multicenter, randomized, double-blind, placebo-controlled trial in 240 clinical centers in 27 countries. Participants included 7736 postmenopausal women with osteoporosis. Patients were randomized to receive either a single 15-minute i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 21 publications
0
13
0
3
Order By: Relevance
“…Interestingly, there is a study in the bone literature demonstrating that zoledronate improved back pain in a clinical trial, and this was independent of changes in bone mass or fracture risk. The mechanism is uncertain but it is reasonable to hypothesize that it may be helping Modic change [68].…”
Section: Weathermentioning
confidence: 98%
“…Interestingly, there is a study in the bone literature demonstrating that zoledronate improved back pain in a clinical trial, and this was independent of changes in bone mass or fracture risk. The mechanism is uncertain but it is reasonable to hypothesize that it may be helping Modic change [68].…”
Section: Weathermentioning
confidence: 98%
“…However, there is little data directly assessing the effects of bisphosphonate treatment on HRQL in postmenopausal women with osteoporosis. In an analysis of the HORIZON-PFT trial, patients treated with ZOL experienced significantly fewer days of limited activity caused by back pain or fracture compared to those receiving a placebo [28]. And it has been reported that ZOL therapy also reduces the number of bed days due to a fracture [29].…”
Section: Prace Oryginalnementioning
confidence: 99%
“…Из-за бо-язни боли пациенты вынуждены осторожно двигаться, что приводит к ухудшению физического состояния, детрениро-ванности и даже беспомощности. По данным недавно опуб-ликованного анализа данных HORIZON-PFT [78], терапия золедроновой кислотой 5 мг по сравнению с плацебо в тече-ние 3 лет значительно снижала количество дней ограниче-ния активности вследствие боли в спине (61 против 72; p=0,0076) или переломов (6 против 10; p=0,001). По сравне-нию с плацебо в группе лечения на 6% меньше женщин от-метили боль в спине, длящуюся 7 дней и более.…”
Section: показанияunclassified